Artificial intelligence support in MR imaging of incidental renal masses: an early health technology assessment - Marka, Alexander Wolfgang; Luitjens, Johanna; Gassert, Florian T.; Steinhelfer, Lisa; Burian, Egon; Rübenthaler, Johannes; Schwarze, Vincent; Froelich, Matthias F.; Makowski, Marcus R.; Gassert, Felix (European radiology, 2024)
OBJECTIVE: This study analyzes the potential cost-effectiveness of integrating an artificial intelligence (AI)-assisted system into the differentiation of incidental renal lesions as benign or malignant on MR images during follow-up. - MATERIALS AND METHODS: For estimation of quality-adjusted life years (QALYs) and lifetime costs, a decision model was created, including the MRI strategy and MRI + AI strategy. Model input parameters were derived from recent literature. Willingness to pay (WTP) was set to $100,000/QALY. Costs of